2019
DOI: 10.1016/j.addr.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic and chronic toxicity evaluation of inorganic nanoparticles for delivery applications

Abstract: Inorganic nanoparticles provide the opportunity to localize bioactive agents to the target sites and protect them from degradation. In many cases, acute toxicities of inorganic nanoparticles used for delivery applications have been investigated. However, little information is available regarding the long-term toxicity of such materials. This review focuses on the importance of subchronic and chronic toxicity assessment of inorganic nanoparticles investigated for delivery applications. We have attempted to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 263 publications
0
98
0
Order By: Relevance
“…The methods of mass-spectrometry, electronic microscopy and radioisotope assay [8,28,29] demonstrated that liver was one of the organs, depositing a considerable amount of nano-ТіО 2 . At the sometime, numerous studies using laboratory animals indicate that in vivo the burdening of the organism with nano-ТіО 2 is accompanied with inflammatory reactions and size-, polymorph-and time-dependent disruptions in the functioning of internal organs (including liver, kidneys, spleen, heart muscle and reproductive glands) [28,[30][31][32]. For instance, according to the data of E. Abbasi-Oshaghi et al [33], the application of ТіО 2 in the concentrations of 10-100 mg/kg for 30 days conditioned a considerable increase in the activity of ALT and AST and in the concentration of total bilirubinin blood plasma of rats, and these effects were accompanied with a considerable inhibition of the expression of antioxidant protection genes (super oxide dismutase, glutathione peroxidase, catalase) and enhanced expression of proapoptotic genes (Bax and р53) and decreased expression of antiapoptotic genes (Bcl2) in liver tissue; the effect of effector caspases in the homogenate of hepatocytes also increased considerably.…”
Section: Resultsmentioning
confidence: 99%
“…The methods of mass-spectrometry, electronic microscopy and radioisotope assay [8,28,29] demonstrated that liver was one of the organs, depositing a considerable amount of nano-ТіО 2 . At the sometime, numerous studies using laboratory animals indicate that in vivo the burdening of the organism with nano-ТіО 2 is accompanied with inflammatory reactions and size-, polymorph-and time-dependent disruptions in the functioning of internal organs (including liver, kidneys, spleen, heart muscle and reproductive glands) [28,[30][31][32]. For instance, according to the data of E. Abbasi-Oshaghi et al [33], the application of ТіО 2 in the concentrations of 10-100 mg/kg for 30 days conditioned a considerable increase in the activity of ALT and AST and in the concentration of total bilirubinin blood plasma of rats, and these effects were accompanied with a considerable inhibition of the expression of antioxidant protection genes (super oxide dismutase, glutathione peroxidase, catalase) and enhanced expression of proapoptotic genes (Bax and р53) and decreased expression of antiapoptotic genes (Bcl2) in liver tissue; the effect of effector caspases in the homogenate of hepatocytes also increased considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, new efforts are also being made to assess the subchronic and chronic toxicity of inorganic nanoparticles, including iron oxide [183]. Chronic safety evaluation of the nanocarriers is important because a common concern over the use of nanocarriers is that the oxidation of the corona protein formed during the interaction between the nanoparticle and the physiological environment will induce oxidative stress to the cells, and the chronic oxidative stress imbalance will exert harmful effects [184,185].…”
Section: Safetymentioning
confidence: 99%
“…The pH of proximal small intestine is 6.5 and in the cecum it is about 6.4 while the transverse colon has a pH of 6.6 and descending colon has a pH of about 7.0. 64 Table 2 shows the commonly used pH dependent polymers for various drugs in colon drug delivery. 65 Eudragit L 100 and Eudragit S 100 are solid white powders with faint characteristic odor and they are chemically anionic copolymers based on methacrylic acid and methyl methacrylate while Eudragit RS 100 is a solid colorless, clear to cloudy granules with faint amine like odor and chemically a copolymer of ethyl acrylate, methyl methacrylate and a low content of methacrylic acid ester with quaternary ammonium groups.…”
Section: Ph Responsive Systemmentioning
confidence: 99%